2022
DOI: 10.3847/1538-4357/ac7fed
|View full text |Cite
|
Sign up to set email alerts
|

Bridging Optical and Far-infrared Emission-line Diagrams of Galaxies from Local to the Epoch of Reionization: Characteristic High [O iii] 88 μm/SFR at z > 6

Abstract: We present photoionization modeling of galaxy populations at z ∼ 0, 2, and >6 to bridge optical and far-infrared (FIR) emission-line diagrams. We collect galaxies with measurements of optical and/or FIR ([O iii] 88 μm and [C ii] 158 μm) emission-line fluxes and plot them on the [O iii ]λ5007/Hβ–[N ii ]λ6585/Hα (BPT) and L([O iii]88)/SFR–L([C ii ]158)/SFR diagrams, where SFR is the star for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 141 publications
2
10
0
Order By: Relevance
“…high U ion ), high sSFR (i.e., undergoing a bursty event or a young stellar age), high FIR [O iii]/[O i] (i.e., large volume fraction of ionized gas to neutral gas), and low metallicity. The result that high [O iii]/[C ii] shows high ionization parameters and burstiness is consistent with Harikane et al (2020), Sugahara et al (2022), andAlgera et al (2023), respectively. We do not observe a strong correlation between [O iii]/[C ii] and T d (but see Walter et al 2018;Algera et al 2023).…”
Section: Characteristics Of High [O Iii]-to-[c Ii] Galaxiessupporting
confidence: 70%
See 1 more Smart Citation
“…high U ion ), high sSFR (i.e., undergoing a bursty event or a young stellar age), high FIR [O iii]/[O i] (i.e., large volume fraction of ionized gas to neutral gas), and low metallicity. The result that high [O iii]/[C ii] shows high ionization parameters and burstiness is consistent with Harikane et al (2020), Sugahara et al (2022), andAlgera et al (2023), respectively. We do not observe a strong correlation between [O iii]/[C ii] and T d (but see Walter et al 2018;Algera et al 2023).…”
Section: Characteristics Of High [O Iii]-to-[c Ii] Galaxiessupporting
confidence: 70%
“…Hashimoto et al (2019) compiled a sample of galaxies with [O iii]/[C ii] at z > 6, and found that UV-selected galaxies in the EoR typically show [O iii]/[C ii] ∼ 3 − 10 or higher (see also Laporte et al 2019;Bakx et al 2020;Harikane et al 2020;Carniani et al 2020;Witstok et al 2022). These values are higher than the typical values of local spirals (∼ 0.5; Brauher et al 2008) and low-metallicity dwarf galaxies (∼ 2; Madden et al 2013;Cormier et al 2015) observed by ISO and Herschel, respectively, suggesting unusual conditions of the ISM in high-z galaxies (e.g., Sugahara et al 2022).…”
Section: Introductionmentioning
confidence: 65%
“…While in nearby starburst galaxies the [CII] line is the dominant coolant of the ISM (i.e., 𝐿 [OIII] /𝐿 [CII] < 1; De Looze et al 2014;Díaz-Santos et al 2017), at high redshift [OIII] is observed to become more luminous (Carniani et al 2020;Harikane et al 2020;Witstok et al 2022). This has been attributed to a highly ionized ISM resulting from strong starburst activity (Inoue et al 2016;Ferrara et al 2019;Arata et al 2020;Vallini et al 2021;Sugahara et al 2022), possibly in combination with other effects such as a low metallicity and/or a low carbon abundance resulting from a top-heavy initial mass function (IMF; e.g., Arata et al 2020;Lupi & Bovino 2020;Katz et al 2022).…”
mentioning
confidence: 99%
“…shows high ionization parameters and burstiness is consistent with Harikane et al (2020), Sugahara et al (2022), andAlgera et al (2023), respectively. We do not observe a strong correlation between [O III]/[C II] and T d (but see Walter et al 2018;Algera et al 2023).…”
Section: Characteristics Of Highmentioning
confidence: 59%
“…Inoue et al (2016) at z > 6, and found that UV-selected galaxies in the EoR typically show [O III]/[C II] ∼ 3-10 or higher (see also Laporte et al 2019;Bakx et al 2020;Carniani et al 2020;Harikane et al 2020;Witstok et al 2022). These values are higher than the typical values of local spirals (∼0.5; Brauher et al 2008) and low-metallicity dwarf galaxies (∼2; Madden et al 2013;Cormier et al 2015) observed by ISO and Herschel, respectively, suggesting unusual conditions of the ISM in high-z galaxies (e.g., Sugahara et al 2022).…”
Section: Introductionmentioning
confidence: 62%